2015
DOI: 10.1111/eci.12386
|View full text |Cite
|
Sign up to set email alerts
|

Transient cardiac injury during H7N9 infection

Abstract: H7N9 virus exerts a transient impairment on the cardiovascular system. Patients with a higher APACHE II score are more susceptible to cardiac damage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 22 publications
1
16
0
8
Order By: Relevance
“…11–13 Similarly, acute myocardial injury has been demonstrated in 7.2%–12% of patients with COVID-19 in preliminary reports, 8 14 with a higher prevalence among those requiring intensive care. Troponin elevation was transient in some studies 13 and associated with reversible subclinical left ventricular diastolic impairment in SARS, 3 suggesting that it may be an innocent bystander phenomenon. However, patients with COVID-19 frequently present with initial cardiovascular symptoms, such as palpitations and chest tightness, 4 and fulminant myocarditis has been reported as a cause of death, 15 suggesting a complex interaction between this respiratory virus and the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…11–13 Similarly, acute myocardial injury has been demonstrated in 7.2%–12% of patients with COVID-19 in preliminary reports, 8 14 with a higher prevalence among those requiring intensive care. Troponin elevation was transient in some studies 13 and associated with reversible subclinical left ventricular diastolic impairment in SARS, 3 suggesting that it may be an innocent bystander phenomenon. However, patients with COVID-19 frequently present with initial cardiovascular symptoms, such as palpitations and chest tightness, 4 and fulminant myocarditis has been reported as a cause of death, 15 suggesting a complex interaction between this respiratory virus and the cardiovascular system.…”
Section: Discussionmentioning
confidence: 99%
“…10 Troponin is a widely accepted biomarker of myocardial injury, and elevated serum levels have been a notable feature during recent epidemics of respiratory virus infections. [11][12][13] Similarly, acute myocardial injury has been demonstrated in 7.2%-12% of patients with COVID-19 in preliminary reports, 8 14 with a higher prevalence among those requiring intensive care. Troponin elevation was transient in some studies 13 and associated with reversible subclinical left ventricular diastolic impairment in SARS, 3 suggesting that it may be an innocent bystander phenomenon.…”
Section: Special Populationsmentioning
confidence: 99%
“…Little is known about the role of STE in the evaluation of IVI-related myocarditis. Han et al evaluated cardiac injury caused by avian-origin influenza A virus (H7N9) infection and observed that patients who developed cardiovascular complications, including overt heart failure, had elevated cardiac troponin I and decreased GLS [27]. With the results of their study taken into account, our finding of GLS remaining unchanged during follow-up may not be surprising.…”
Section: Discussionmentioning
confidence: 75%
“…Though this may contrast with a study done by Lewes et al where myocarditis and myalgia occurred in two out of seven patients with mild influenza infection, the very small sample size of Lewes et al study warrants more studies to confirm the results and is misleading [26]. A study by Han et al showed that out of 40 patients infected with lab-confirmed avian-influenza A H7N9, half of the patients presented with cardiovascular complications like hypotension (47.5%) and heart failure (40.0%) but the infection by H7N9 is common in birds and less common in humans [35].…”
Section: Figure 1: Studies On Influenza Myocarditis (Mortality and Numentioning
confidence: 98%